Anaerobic digestion of waste from leather industry: biogas production potential by bench and pilot scale experiments - Džajić Valjevac, Melina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Evaluates biogas generation from leather industry waste through bench-scale and pilot-scale anaerobic digestion. Results demonstrate stable biogas production potential while managing ammonia and sulfide concentrations within acceptable ranges.